Asymmetric synthesis of chiral imidazolidines by merging copper and visible light-induced photoredox catalysis. Issue 11 (26th April 2022) - Dai, Linlong; Zhu, Qiaohong; Zeng, Jie; Liu, Yuheng; Zhong, Guofu; Han, Xiaoyu; Zeng, Xiaofei
Abstract : A visible light induced copper catalyzed synthesis of decarboxylative radical coupling/cyclization reaction for the synthesis of chiral imidazolidines in high yields and enantioselectivities was reported. Abstract : Chiral imidazolidine shows its potential in multiple fields. However, direct catalytic asymmetric construction of chiral imidazolidines is still limited. Herein, we report an effective chiral bisoxazoline copper-induced and photoredox-catalyzed strategy for the synthesis of chiral imidazolidines based on the decarboxylative radical coupling/cyclization reaction of simple glycine derivatives, aldehydes and imines. Various imidazolidines were conditionally accessed with high yields (up to 96%) and enantioselectivities (up to 95% ee). Furthermore, this strategy could also be applied in the synthesis of chiral vicinal diamines by varying the reaction conditions.